IKAP deficiency in an FD mouse model and in oligodendrocyte precursor cells results in downregulation of genes involved in oligodendrocyte differentiation and myelin formation. - David Cheishvili (Public Library of Science (PLoS), 2014)
The splice site mutation in the IKBKAP gene coding for IKAP protein leads to the tissue-specific skipping of exon 20, with concomitant reduction in IKAP protein production. This causes the neurodevelopmental, autosomal-recessive genetic disorder - Familial Dysautonomia (FD). The molecular hallmark of FD is the severe reduction of IKAP protein in the nervous system that is believed to be the main reason for the devastating symptoms of this disease. Our recent studies showed that in the brain of two FD patients, genes linked to oligodendrocyte differentiation and/or myelin formation are significantly downregulated, implicating IKAP in the process of myelination. However, due to the scarcity of FD patient tissues, these results awaited further validation in other models. Recently, two FD mouse models that faithfully recapitulate FD were generated, with two types of mutations resulting in severely low levels of IKAP expression. Here we demonstrate that IKAP deficiency in these FD mouse models affects a similar set of genes as in FD patients' brains. In addition, we identified two new IKAP target genes involved in oligodendrocyte cells differentiation and myelination, further underscoring the essential role of IKAP in this process. We also provide proof that IKAP expression is needed cell-autonomously for the regulation of expression of genes involved in myelin formation since knockdown of IKAP in the Oli-neu oligodendrocyte precursor cell line results in similar deficiencies. Further analyses of these two experimental models will compensate for the lack of human postmortem tissues and will advance our understanding of the role of IKAP in myelination and the disease pathology.